PENGARUH KOMPENSASI DAN JOB INSECURITY TERHADAP TURNOVER INTENTION KARYAWAN PT. NUSANTARA SURYA SAKTI KOTA TERNATE - Muhammad Asril Arilaha; Mardiyani Gani (Jurnal Manajemen Sinergi, 2017)
This study aims to determine the effect of compensation and job insecurity to employee turnover intention. This research was conducted at PT. Nusantara Surya Sakti Ternate City.  This research is expected to be used as material information and consideration to find solution to turnover problem that happened in company. The samples used in this study were 83 respondents, with sampling using proportionate stratified random sampling technique and using multiple regression analysis method. The results of this study found that the compensation variable has a negative and significant effect on employee turnover intention. Job Insecurity has a positive and significant impact on employee turnover intention.With the value of R square (R2) of 0.369 or 36.9%